2018
DOI: 10.15570/actaapa.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age at onset and clinical characteristics of Behçet’s disease

Abstract: Introduction: This study compares the clinical characteristics and treatment modalities of Behçet's disease patients by age of onset at the Dr. Tidjani Damerdji University Hospital Center in Tlemcen, Algeria. Methods: Data from patients treated for Behçet's disease between January 1990 and December 2016 were analyzed retrospectively. All patients that fulfilled the diagnostic criteria laid down by the International Study Group for Behçet's Disease were included in the study. Patients with early-onset disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The definition of early-onset and late-onset ABD and the clinical characteristics differ among studies, which may partially explain the conflicting results reported. 3 Juvenile disease is with 2%-21% in different populations less frequent 15 and late-onset ABD is with 7%, as shown in this study, even less common. Late-onset ABD exhibits with 57% a slight androtropism, with recurrent oral ulcers, genital ulcers, ocular lesions and a positive pathergy test as clinical signs with a prevalence of ≥45%.…”
Section: Late-onset Adamantiades-behçet's Disease-systematic Review A...supporting
confidence: 69%
See 2 more Smart Citations
“…The definition of early-onset and late-onset ABD and the clinical characteristics differ among studies, which may partially explain the conflicting results reported. 3 Juvenile disease is with 2%-21% in different populations less frequent 15 and late-onset ABD is with 7%, as shown in this study, even less common. Late-onset ABD exhibits with 57% a slight androtropism, with recurrent oral ulcers, genital ulcers, ocular lesions and a positive pathergy test as clinical signs with a prevalence of ≥45%.…”
Section: Late-onset Adamantiades-behçet's Disease-systematic Review A...supporting
confidence: 69%
“…The gradual frequency of erythema nodosum with age probably might explain the wide range of this sign reported in different ABD studies (15%-78%). 1 Since the frequency of ocular and vascular lesions has been associated with the occurrence of erythema nodosum, 13,17 it should be expected that the frequency of ocular and vascular lesions might also vary in different studies (29%-100%) 3,4,17 and might be less frequent in late-onset ABD, as found in our study. Vascular lesions are not common in ABD but they are usually accompanied with severe complications.…”
Section: Late-onset Adamantiades-behçet's Disease-systematic Review A...supporting
confidence: 63%
See 1 more Smart Citation
“…Tugal-Tutkun et al reported anterior uveitis in 11% of cases, posterior uveitis in 28.8%, while panuveitis involvement was seen in 60.2% of their entire cohort of 880 patients (1,567 eyes). Intermediate uveitis in the form of isolated vitritis without anterior or posterior involvement (clinically and angiographically) was also reported more often in early rather than late onset BD ( 31 33 ). However, the latest SUN classification criteria published in 2021 does not include isolated vitritis in its diagnostic criteria, rather in association with anterior, posterior or panuveitis ( 34 ).…”
Section: Ocular Behçet's Clinical Presentationsmentioning
confidence: 92%
“…Both the anterior and posterior segments can be affected but panuveitis is the most frequent presentation. In addition, intermediate uveitis in the form of isolated vitritis is more common in early BD than late BD [42]. Episcleritis, scleritis, conjunctival ulcers, keratitis, orbital inflammation, isolated optic neuritis, and extraocular muscle palsies has been described [13].…”
Section: Diagnosis Of Systemic Behçet's Diseasementioning
confidence: 99%